Evaluation of the effect of nurse education on patient-reported foot checks and foot care behaviour of people with diabetes receiving haemodialysis - Brand, Sarah L.; Musgrove, A.; Jeffcoate, W.J.; Lincoln, Nadina B. (Wiley Online Library, 2016)
AIMS: To assess whether a programme of nurse education increased the frequency with which nurses conducted foot checks on people with diabetes undergoing haemodialysis and to evaluate whether this influenced self-reported foot care behaviour. METHODS:A non-randomized stepped-wedge design was used to evaluate a nurse education programme implemented in four UK National Health Service dialysis units. People with diabetes undergoing haemodialysis were invited to complete a questionnaire on the frequency of foot examination by health professionals, on the presence of foot problems and on their own foot care behaviour, using the Nottingham Assessment of Functional Foot-care (NAFF). An education session for nurses, including procedures for foot examination, was conducted sequentially in each of four haemodialysis units. The questionnaire was repeated at 2-monthly intervals. RESULTS:The education session resulted in a significant increase in the reported number of foot examinations by nurses (P = 0.007). There was also a significant improvement in reported foot care behaviour (P < 0.001), but this occurred between the first and second 2-monthly assessments and was unrelated to the timing of the intervention. CONCLUSIONS: A single education session can improve the routine checking of the feet of people with diabetes undergoing haemodialysis. The administration of the Nottingham Assessment of Functional Foot-care questionnaire was associated with improved self-reported foot care behaviour, reflecting greater awareness of risk in this population.